Cortical Visual Impairment in CDKL5 Deficiency Disorder - Quintiliani, Michela; Ricci, Daniela; Petrianni, Maria; Leone, Simona; Orazi, Lorenzo; Amore, Filippo; Gambardella, Maria Luigia; Contaldo, Ilaria; Veredice, Chiara; Perulli, Marco; Musto, Elisa; Mercuri, Eugenio Maria; et al. (Frontiers in Neurology, 2022)
Background CDKL5 deficiency disorder (CDD) is a developmental encephalopathy caused by pathogenic variants in the gene cyclin-dependent kinase-like 5. Cerebral Visual impairment (CVI) is frequent in CDD patients.The aim of our study was to evaluate clinical and electrophysiological profile of CVI in patients with CDD, in order to correlate various aspects of visual function to neurodevelopmental and epileptic features. Methods The study included all patients with CDD from the National Pathology Registry. All patients underwent neurological examination, a disease specific functional assessment, structured clinical evaluation of visual functions, including Pattern Reversal VEP and a detailed monitoring of epileptic features, including video-EEG. Results All the 11 patients recorded in the CDKL5 national registry, 10 females and 1 male, age range 1.5 to 24 years (mean 9, SD 7.7, Median 6.5) were enrolled. Visual function is impaired in all patients, in particular visual fields, visual acuity, contrast sensitivity and stereopsis, were consistently abnormal while other aspects, such as fixing and tracking, were relatively preserved. Pattern Reversal VEP were abnormal in nearly 80% of our patients. No correlation was found between CVI severity, age, level of psychomotor development, EEG abnormalities or pathology stages even if an overall less abnormal EEG pattern was more often associated with better visual results. Conclusion In conclusion, CVI can be considered a major feature of CDD with a diffuse involvement of several behavioral and electrophysiological aspects. Larger cohorts will help to better clarify the possible prognostic role of EEG severity in predicting both visual and developmental abnormalities.